The information support of the contract of passenger’s carriage by air - Мамчур, Л. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The author analyzes the information component of the legal relationship between the passenger and thecarrier based on the contract of passenger’s carriage by air, clears up the matter of its importance for theproper exercise of the rights and duties from the contract. Special attention is paid to the forms and methodsof information exchange between the subjects at different stages of the contract.